The Use Of First Language In Elt for Indonesian Young Learner: Efl Teachers’ Perspectives - Zakaria Bintang Pamungkas (Hikamatzu | Journal of Multidisciplinary, 2025)
The use of first language (L1) in English Language Teaching (ELT) for young learners has been being a long-standing pedagogical debate. While traditional approaches often encourage exclusive use of English, in contexts such as Indonesia where English is a foreign language, young learners may get benefit from occasional L1 support. However, research focusing on teachers’ perspectives in this area remains limited, especially in the Indonesian EFL setting. This study addresses this gap by exploring how Indonesian EFL teachers perceive and implement L1 in teaching English to young learners. The study aimed to investigate teachers’ beliefs about the functions, advantages, and challenges of using L1, as well as the extent to which it facilitates or hinders language acquisition. Employing a qualitative descriptive design, data were collected through semi-structured interviews and classroom observations involving 3 EFL teachers from Islamic elementary schools in Ponorogo. The data were analyzed thematically to identify recurring patterns and insights. The findings reveal that most teachers perceive L1 as a useful pedagogical tool for clarifying difficult concepts, giving instructions, managing classroom discipline, and reducing learners’ anxiety. However, they also express concern that excessive reliance on L1 may limit students’ exposure to English and hinder the development of communicative competence. The novelty of this study lies in highlighting the nuanced perspectives of Indonesian EFL teachers, which demonstrate a balanced view between the practical necessity and the potential drawbacks of L1 use in ELT for young learners. The study concludes that strategic and judicious use of L1 can serve effective English learning, provided it is accompanied by opportunities for meaningful English exposure and practice.